Menilai Kelayakan Harga Saham Bank-Bank Syariah di Indonesia Melalui Pendekatan Relative Valuation - Widya Antikasari, Tiara; Pramesti, Dyah (Journal Of Islamic Economics And Finance, 2023)
The purpose of this study was to determine the intrinsic value of BRIS and BTPS issuer shares using a relative valuation approach which was analyzed using two methods, price earning ratio (PER) method and price to book value (PBV) method. Results of existing valuation analysis are used as a guide in making investment decisions by comparing the intrinsic value and the market price. This research belongs to the descriptive quantitative research with the type of data used is secondary data in the form of historical stock price data for the last 5 years, earnings per share (EPS) and average PER value data, and current book value per share (current BVPS) and the average PBV value of BRIS and BTPS. The results of the study show that BRIS and BTPS shares which are valued using PER method and PBV method indicate that the two bank shares are undervalued, which means that their stock prices tend to be cheap, so that both BRIS and BTPS shares are worth buying.